2018
DOI: 10.1186/s12889-018-5607-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with type 2 diabetes mellitus and hypertension among the hill tribe elderly populations in northern Thailand

Abstract: BackgroundType 2 diabetes mellitus (T2DM) and hypertension (HT) are major noncommunicable health problems in both developing and developed countries, including Thailand. Each year, a large amount of money is budgeted for treatment and care. Hill tribe people are a marginalized population in Thailand, and members of its elderly population are vulnerable to health problems due to language barriers, lifestyles, and daily dietary intake.MethodsAn analytic cross-sectional study was conducted to estimate the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 39 publications
6
39
2
Order By: Relevance
“…This is similar to a study in South Africa [38] and Benghazi [17, 38]. However, there are reports against our study finding [39]. The possible reason for males to get ISH could be due to males have higher cardiac output than females.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to a study in South Africa [38] and Benghazi [17, 38]. However, there are reports against our study finding [39]. The possible reason for males to get ISH could be due to males have higher cardiac output than females.…”
Section: Discussionsupporting
confidence: 92%
“…Oladapo et al found a prevalence of 20.8% in also important to note that the latter study was carried a rural population composed mainly of farmers, out several years before ours. More recent studies in artisans and traders (18) while Onwubere et al found rural areas however reported higher prevalence rates, an even higher rate of 46.4% (19). These are higher though lower than what we found.…”
Section: Discussionmentioning
confidence: 94%
“…Another reason might be an increase in the number of people who are exposed to people outside their village (17.1%). Today, many hill tribe people prefer to work outside of their village to earn money to support their family [36]. In fact, hill tribe people, particularly those aged below 25 years, should have low HBsAg since they were born after the implementation of HBV vaccination in Thailand.…”
Section: Discussionmentioning
confidence: 99%